2016
DOI: 10.7717/peerj.1896
|View full text |Cite
|
Sign up to set email alerts
|

Job satisfaction and intention to quit: an empirical analysis of nurses in Turkey

Abstract: The aim of this study was to identify the facets influencing job satisfaction and intention to quit of nurses employed in Turkey. Using a non-probability sampling technique, 417 nurses from six large private hospitals were surveyed from March 2014 to June 2014. The nurses’ demographic data, their job-related satisfaction and turnover intentions were recorded through a self-administered questionnaire. In this study, descriptive and bivariate analyses were used to explore data, and multivariate analysis was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

25
110
2
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(164 citation statements)
references
References 51 publications
25
110
2
9
Order By: Relevance
“…There was a positive significant correlation between subscales of JSS with total job satisfaction. This was consistent with a study in Cross River State Nigeria and Turkey [8,13], where positive and significant correlation was seen.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…There was a positive significant correlation between subscales of JSS with total job satisfaction. This was consistent with a study in Cross River State Nigeria and Turkey [8,13], where positive and significant correlation was seen.…”
Section: Discussionsupporting
confidence: 81%
“…Thus, female's ratings of job satisfaction were significantly higher than male nurses at (t=-2.196, p=0.03).This was consistent with a study in Turkey [8], where female nurses slightly more satisfied than male nurses. The possible explanation might be nursing still perceived to be a job for females rather than males.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Therefore, the job satisfaction of Indonesian nurses was at moderate level. This result is consistent with several studies on nurses' job satisfaction [26][27][28]. The present research also concluded that job satisfaction among nurses is significantly and negatively associated with intention to quit.…”
Section: Discussionsupporting
confidence: 93%